A Mobile Application For Personalised Car Information (Journal of Digital System Development, 2024)
The high rate of car ownership in Malaysia may lead to difficulties for owners in remembering all the details of their vehicles. Therefore, an application called CarBuddy, which provides personalised information about users' cars, would help them manage and maintain their vehicles more efficiently. The project adopted a waterfall methodology during the application development to produce a prototype based on the requirements gathered during the analysis phase. Field-testing for the application involved 30 participants who installed the application and provided feedback through a questionnaire distributed via Google Forms after using the application. The respondents’ feedback is based on four dimensions of the prototype: user-friendliness, usefulness, ease of learning, and satisfaction. The test's overall result indicates that most respondents are satisfied with this application. Usability tests revealed that the application significantly improved the user experience by providing reminders and detailed insights into vehicle performance. This application can benefit car owners in Malaysia by enhancing vehicle maintenance and the overall user experience.